The UV-Vis spectrum of antioxidant complex from frozen-dried egg white protein and tomato extract - Siti Imama Khoiriyah; Mohammad Mabrur; Sutiman Bambang Sumitro; Sri Widyarti (The East Java Biological Society, 2020)
In this study, we want to characterize egg white protein-tomato extract complex based on the UV-Vis spectrum. The formulation of antioxidant complex Non-Freeze-drying (NFD) was made at a ratio of 1:10 (v/v) while the Freeze-drying (FD) sample was made at a ratio of 1:2 (v/v). The results showed that the absorption peak of FD complex profile value was lower than the single ingredient, while the tomato extract was higher than the complex profile. On the contrary, the NFD complex showed a higher peak absorption value than to every single ingredient. Based on each UV-Vis spectrum profile, the tomato extract profile shifted the absorption peak, and the absorbance value of the FD sample was changing higher than the NFD sample, while the egg white protein spectrum profile did not change significantly in the FD and NFD samples. The absorption peak of the complex is higher than the single ingredient indicated that the characterization of the complex had been formed. In the NFD complex profile, the absorption peaks formed at the wavelength regions of 230 nm and 280 nm with absorbance values of 2.51 and 0.76 and its number has higher than those of the FD complex with absorbance values of 2.47 and 1.82 at wavelengths of 220 and 265 nm.